Challenges in Jewish-Christian relations - Aitken, J. K.; Kessler, Edward; Aitken, J. K. (Studies in Judaism and Christianity, 2006)
Introduction / James K. Aitken and Edward Kessler -- Jews facing Christians : the burdens and blinders from the past / Marc Saperstein -- The Bible in future Jewish-Christian relations / John F.A. Sawyer -- The Orthodox churches in dialogue with Judaism / Nicholas de Lange -- Jewish-Russian Orthodox Christian dialogue / Irina Levinskaya -- Catholic-Jewish agendas / Remi Hoeckman -- Institutional relations in Jewish-Christian relations / Friedhelm Pieper -- The new Europe, nationalism, and Jewish-Christian relations / David Weigall -- Israel within Jewish-Christian relations / Andrew P.B. White -- The effect of the Holocaust on Jewish-Christian relations / Stephen D. Smith -- A third epoch : the future of discourse in Jewish-Christian relations / Peter Ochs and David F. Ford -- Women's voices in Jewish-Christian relations / Christine Trevett -- Considering a Jewish statement on Christianity / Edward Kessler and James K. Aitken -- Dabru emet -- Dabru emet and its significance / Edward Kessler -- What does Christianity in Jewish terms mean? / James K. Aitken -- Jewish-Christian relations in the interfaith encounter / Martin Forward